Offending, custody and opioid substitution therapy treatment utilisation among opioid-dependent people in contact with the criminal justice system: Comparison of Indigenous and non-Indigenous Australians - Gisev, N.; Gibson, A.; Larney, S.; Kimber, J.; Williams, M.; Clifford, A.; Doyle, M.; Burns, L.; Butler, Tony; Weatherburn, D.; Degenhardt, L. (2014)
© 2014 Gisev et al.; licensee BioMed Central Ltd. Background: Although Indigenous Australians are over-represented among heroin users, there has been no study examining offending, time in custody, and opioid substitution therapy (OST) treatment utilisation among Indigenous opioid-dependent (including heroin) people at the population level, nor comparing these to non-Indigenous opioid-dependent people. The aims of this study were to compare the nature and types of charges, time in custody and OST treatment utilisation between opioid-dependent Indigenous and non-Indigenous Australians in contact with the criminal justice system. Methods: This was a population-based, retrospective data linkage study using records of OST entrants in New South Wales, Australia (1985-2010), court appearances (1993-2011) and custody episodes (2000-2012). Charge rates per 100 person-years were compared between Indigenous and non-Indigenous Australians by sex, age and calendar year. Statistical comparisons were made for variables describing the cumulative time and percentage of follow-up time spent in custody, as well as characteristics of OST initiation and overall OST treatment utilisation. Results: Of the 34,962 people in the cohort, 6,830 (19.5%) were Indigenous and 28,132 (80.5%) non-Indigenous. Among the 6,830 Indigenous people, 4,615 (67.6%) were male and 2,215 (32.4%) female. The median number of charges per person against Indigenous people (25, IQR 31) was significantly greater than non-Indigenous people (9, IQR 16) (p < 0.001). Overall, Indigenous people were charged with 33.2% of the total number of charges against the cohort and 44.0% of all violent offences. The median percentage of follow-up time that Indigenous males and females spent in custody was twice that of non-Indigenous males (21.7% vs. 10.1%, p < 0.001) and females (6.0% vs. 2.9%, p < 0.001). The percentage of Indigenous people who first commenced OST in prison (30.2%) was three times that of non-Indigenous people (11.2%) (p < 0.001). Indigenous males spent less time in OST compared to non-Indigenous males (median percentage of follow-up time in treatment: 40.5% vs. 43.1%, p < 0.001). Conclusions: Compared to non-Indigenous opioid-dependent people, Indigenous opioid-dependent people in contact with the criminal justice system are charged with a greater number of offences, spend longer in custody and commonly initiate OST in prison. Hence, contact with the criminal justice system provides an important opportunity to engage Indigenous people in OST.